Clinicoetiological Characterization of Infectious Vaginitis amongst Women of Reproductive Age Group from Navi Mumbai, India. (17th August 2015) - Narayankhedkar, Anuradha; Hodiwala, Anahita; Mane, Arati
Abstract : Vaginitis is one of the commonest reproductive tract infections in sexually active women. In the present study clinicoetiological characterization of infectious vaginitis amongst 380 women of reproductive age group (18–45 years) was done. Bacterial vaginosis (BV) was detected by Nugent's scoring, Candida infection by culture, and trichomoniasis (TV) by wet mount. One hundred and ten (28.9%) women presented with symptoms of vaginitis. The presenting symptoms were vaginal discharge 106 (96.4%), vulval itching/irritation 19 (17.3%), malodor 5 (4.5%), pain in abdomen 3 (2.7%), and dysuria 1 (0.9%). The commonest etiology detected was Candida in 33 (30%) cases, of which 18 (54.5%) were C. albicans and 15 (45.5%) non- albicans Candida (NAC) infections. The NAC isolates were C. glabrata (n = 10 ), C. tropicalis (n = 3 ), and C. krusei (n = 2 ). BV and TV were observed in 19 (17.3%) and 2 (1.8%) cases, respectively. A statistically significant association between Candida infection and presence of curdy-white discharge (p = 0.001 ) and vulval itching/irritation (p = 0.007 ) was noted. To conclude, we observed the etiological predominance of Candida infection, with considerable prevalence of NAC, indicating the need for microbiological investigation up to species level in cases of Candida infections, to ensure appropriate management.